Palm oil and the politics of deforestation in Indonesia - Marco Elías Cisneros Tersitsch; Krisztina Kis-Katos; Nunung Nuryartono (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
This paper studies the interactions between political and economic incentives to foster forest conversion in Indonesian districts. Using a district-level panel data set from 2001 to 2016, we analyze variation in remotely sensed forest loss and forest fires as well as measures of land use licensing. We link these outcomes to economic incentives to expand oil palm cultivation areas as well as political incentives arising before idiosyncratically-timed local mayoral elections. Empirical results document substantial increases in deforestation and forest fires in the year prior to local elections. Additionally, oil palm plays a crucial role in driving deforestation dynamics. Variations in global market prices of palm oil are closely linked to deforestation in areas which are geo-climatically best suited for growing oil palm and they amplify the importance of the political cycle. We thus find clear evidence for economic and political incentives reinforcing each other as drivers of forest loss and land conversion for oil palm cultivation.
Keywords: O13; Q15; Q56; P16; 330; deforestation; palm oil; local election cycles; Indonesia